A model to simulate multidimensional nonstationary and non-Gaussian fields based on S-transform. (October 2021) - Hong, H.P.; Cui, X.Z.; Zhou, W.X.
Highlights: Provided a new model for multidimensional nonstationary and non-Gaussian field S-transform. Proposed a new iterative algorithm to simulate multidimensional nonstationary and non-Gaussian field. Explained the use of the model to simulate surrogates. Showed the application of the proposed algorithm for three practical examples. Abstract: In many cases, the probabilistic assessment of structure and infrastructure systems requires the modeling and simulation of nonstationary or nonhomogeneous and non-Gaussian random fields. In the present study, we propose an iterative algorithm to simulate multidimensional nonstationary and non-Gaussian random fields. It uses the S-transform that has the advantage of providing good time (or space) localized high frequency resolution and good low frequency resolution. The algorithm iteratively adjusts time–frequency (or space-wavenumber) dependent power spectral density function of the nonstationary random field and the amplitude of the random field according to the marginal probability distribution of the field. The algorithm is efficient and usually converges within less than ten iterations for practical problems. The application of the proposed algorithm is shown by three numerical examples of practical interest.